Curcumin-Loaded Organogel for The Topical Skin Disorder Based on 12 Hydroxystearic Acid - Duaa Razzaq Jaafer; Masar Basim Mohsin Mohamed (College of Pharmacy University of Baghdad, 2024)
Curcumin (CUR) possesses various pharmacological properties, including antibacterial and improving injury healing. This work aimed to formulate curcumin organogel using 12 hydroxy stearic acid as gelator with tween 80 as surfactant and PEG 400 as co surfactant to improve the CUR permeation through the skin. The CUR organogels were prepared using different 12HSA concentrations with solvents sesame oil (SO), and orange oil (OO), in addition to T80 and P400 and evaluated for their saturated solubility, tabletop rheology, oil binding capacity, pH, spreadability, in vitro release, antibacterial activity, oscillatory rheology study, skin irritation, histological examination and ex- with in- vivo permeation study across rat abdominal skin. Results: The important results that distinguished organogels were the spreadability and in vitro release studies. The 4SO, 2OO, 2T80, and 10P400 organogels presented successful gelation and represented the lowest 12HSA concentration in each solvent that approached the current aim's study by being more spreadable with higher CUR released. At the same time, the 2T80 and 10P400 gave zones of inhibition to 4 bacterial strains and good viscoelasticity by exhibiting large flow point values in the frequency sweep study compared with 4SO and 2OO. In vivo study affirmed the CUR permeation by studying the fluorescent images of 2T80 and 10P400, and the ex vivo permeation study for 10P400 proved the CUR permeation through rat's skinOur results indicated the potential of 10P400 and 2T80 organogel to improve the topical therapeutic efficacy of CUR.